Study of The Antibacterial Activity of Endophytic Fungus That Colonize With The Twig of Andrographis paniculata - Anshar Al Khairi, Varel; Etika, Sri Benti; Suryelita, Suryelita; Ulfah, Mariam; Riga, Riga (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Reports of the chemical constituents of Andrographis paniculata showed that this plant produced various secondary metabolites with antibacterial activity. Further exploration of bioactive compounds from A. paniculata can also be conducted by analyzing its endophytic fungi. Isolation of endophytic fungi from the twig of A. paniculata obtained three isolates of endophytic fungi. One of the isolates, RS-2, was fermented on rice media and extracted with ethyl acetate to give the EtOAc extract. The EtOAc extract from fungus RS-2 was analyzed for their antibacterial and phytochemical screening. The results exhibiting the EtOAc extract of fungus RS-2 has activity to inhibite bacterial growth. Overall, the study of the antibacterial activity of endophytic fungus obtained from the twig of A. paniculata was firstly carried out in this study